2018
DOI: 10.1016/j.thromres.2018.02.150
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and risk for venous thromboembolism from contemporary therapy for pediatric acute lymphoblastic leukemia

Abstract: In this pediatric ALL cohort, obesity conferred more than a three-fold increased risk for symptomatic VTE. In a subgroup of patients who underwent active screening, up to a third were noted to have VTE (symptomatic and asymptomatic). TEG did not predict VTE. Additional studies are necessary to validate these findings and to further refine a risk-stratified approach to thrombo-prevention during ALL therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 45 publications
4
10
0
Order By: Relevance
“…6 The induction therapy in our patient included L-asparaginase and corticosteroids, and chemotherapy was the primary risk factor in our patient regarding developing CVST during leukemia treatment. A previous study found that obesity was strongly associated with venous thrombosis, 7 and our patient was obese. Another study reported that some patients represented with neurological symptoms and developed CVST 24 days after head injury.…”
Section: Discussionsupporting
confidence: 64%
“…6 The induction therapy in our patient included L-asparaginase and corticosteroids, and chemotherapy was the primary risk factor in our patient regarding developing CVST during leukemia treatment. A previous study found that obesity was strongly associated with venous thrombosis, 7 and our patient was obese. Another study reported that some patients represented with neurological symptoms and developed CVST 24 days after head injury.…”
Section: Discussionsupporting
confidence: 64%
“…16 In this study, most increased risk of TE in ALL. [18][19][20][21][22] In our study, older age was associated with a higher risk of PE. We also observed a greater proportion of male sex in patients with PE.…”
Section: Discussionsupporting
confidence: 56%
“…Asparaginase decreases anticoagulant, procoagulant, and fibrinolytic protein levels, especially reduction in antithrombin results in hypercoagulability and increased risk of thrombosis 17 . Exposure to asparaginase, increasing age, T‐cell leukemia, mediastinal mass, obesity, and use of dexamethasone in induction have previously been pointed out as possible factors for increased risk of TE in ALL 18‐22 . In our study, older age was associated with a higher risk of PE.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Obesity and metabolic dysfunction play a major role in survivors of childhood ALL leading to increased risk of morbidity and mortality throughout their life [3][4][5][6]. Altered lipid metabolism caused by intensive therapy has been addressed [7][8][9][10][11] and contradictory associations to toxicities such as thromboembolism [12][13][14][15], osteonecrosis [16,17] and pancreatitis [18][19][20][21][22][23][24] have been reported. Furthermore, abnormal lipid levels prior to ALL therapy [25][26][27][28][29] and obesity at time of ALL-diagnosis have been associated with reduced efficacy of induction therapy, impaired event-free and overall survival [30][31][32] as well as suggested as a part of the leukomogenisis [33].…”
Section: Introductionmentioning
confidence: 99%